Development of a Higher Education Data Warehouse Using the Data Vault 2.0 Method - Triaji, Bagas; Subagyo, Aloysius Agus; Rifai, Muhammad Arif (Politeknik Ganesha Medan, 2024)
In this research, we investigate the potential of Data Vault 2.0 modeling as a solution to address the complexity of data management in higher education, which is often spread across multiple information systems. The main objective of this research is to confirm the effectiveness of Data Vault 2.0 in building a data warehouse, as well as facilitating the integration of data from different sources, such as the Academic Information System, Personnel Information System, and New Student Admission System. The research method used includes data collection and processing through the staging stage before being stored in the Data Vault structure consisting of hubs, links, and satellites. The research findings show that Data Vault 2.0 not only provides flexibility in development but also allows two developers to work in parallel without interfering with each other, speeding up the data integration process. In addition, the design evaluation results show that Data Vault 2.0 is able to accommodate dynamic changes in requirements, while facilitating the creation of dashboards for data visualization and analysis. The conclusion of this research emphasizes that although Data Vault 2.0 is more complicated than models such as star schema, it provides advantages in flexibility and better data integration. Further research is needed to address the challenges of data integration and deepen the understanding of the implementation of this model in various contexts.